THE EFFECT AUDIT COMMITTEE AND INDEPENDENT COMMISSIONER ON EARNINGS MANAGEMENT - Asrie Dyah; E. Novita; Nikmah Nikmah (UM. Bengkulu, 2026)
This study aimed to examine the effect of audit committee, independent commissioner on earnings management. The sample in this study are banking in Southeast Asia of period 2017- 2021. The data used in this study is secondary data obtained from the financial data at banking website. The number of samples in this study are 52 banks. Data analysis was performed with multiple regression analysis using SPSS version 23. The result showed that audit committee, independent commisioners has no effect on earnings management. Key Words: Earnings Management, Audit Comitte, Independent Commisioners